Volume 6: 12th International Conference on Multibody Systems, Nonlinear Dynamics, and Control 2016
DOI: 10.1115/detc2016-59381
|View full text |Cite
|
Sign up to set email alerts
|

Higher-Order Plate Elements for Large Deformation Analysis in Multibody Applications

Abstract: This study introduces higher-order three-dimensional plate elements based on the absolute nodal coordinate formulation (ANCF) for large deformation multibody applications. The introduced elements employ four to eight nodes and the St. Venant-Kirchhoff material law. A newly proposed eight-node element is carefully verified using various numerical experiments intended to discover possible locking phenomena. In the introduced plate elements, the usage of polynomial approximations of second order in all three dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…( 5) and ( 7), the strain vector is expressed as a function of the position gradient vectors, i.e. (11) and its variation can be related to a mid-surface quantity χ using Eq. ( 2) as…”
Section: Strains and Stressesmentioning
confidence: 99%
See 2 more Smart Citations
“…( 5) and ( 7), the strain vector is expressed as a function of the position gradient vectors, i.e. (11) and its variation can be related to a mid-surface quantity χ using Eq. ( 2) as…”
Section: Strains and Stressesmentioning
confidence: 99%
“…Subsequently, detailed investigations of this element focusing on the formulation of elastic forces were conducted by Yamashita et al [9] employing the continuum mechanics approach and Valkeapää et al [10] using the elastic midsurface approach. Ebel et al [11,12] developed eight-and nine-node higher-order plate elements and demonstrated the benefits of alleviating locking phenomena by introducing higher-order transverse derivatives as nodal variables. The fully parameterized elements ensure C1 continuity at neighboring element nodes, whereas the gradient-deficient elements only guarantee C0 continuity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 423 423 element and studied it intensively. 32 Ebel, Matikainen 33 34 which prevent shear locking but substantially increase the degree of freedom of the elements. Besides, Yu et al 35 proposed a quadrilateral element No.…”
Section: Ancf Plate Finite Elementsmentioning
confidence: 99%
“… 3 423 423 element and studied it intensively. 32 Ebel, Matikainen 33 synthesized three higher-order elements No. 3 433 433, No.…”
Section: Ancf Plate Finite Elementsmentioning
confidence: 99%